Barium Sulfate Aspiration mimicking Tracheo-esophageal Fistula in a 82 years Aged Man - Kana, Pulak Kumar; Bairagya, Tapan Das; Das, Ira; Chatterjee, Surajit (Journal of Medicine, 2013)
No Abstract Available DOI: http://dx.doi.org/10.3329/jom.v14i1.14625 J MEDICINE 2013; 14 : 101-102